Construction method of hard road shoulder of highway

Through the construction method of sliding mold machine paving hard road shoulders and specific materials ratio, the problem of dirt road shoulders being easily damaged under rainwater erosion is solved, the construction efficiency and service life of road shoulders are improved, and the effective utilization of industrial solid waste is realized.

CN119194953APending Publication Date: 2024-12-27DEZHOU HIGHWAY ENG CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411058853.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The dirt shoulders of existing highways are easily damaged under the erosion of rain, resulting in road gullies and collapse, affecting road safety and traffic.

Method used

The construction method adopts the sliding mold machine and specific material ratio, including cleaning and leveling, preparing materials (asphalt mixing station tail dust, cement, sand, water) and paving hard shoulders through the sliding mold machine, with a thickness of 80-200mm, followed by Perform embossing operations and install expansion joints to improve friction performance and crack resistance.

Benefits of technology

It greatly improves construction efficiency, extends the service life of hard road shoulders, reduces costs, and reduces environmental pollution through the large-scale utilization of industrial solid waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194953A_ABST
    Figure CN119194953A_ABST
Patent Text Reader

Abstract

The invention provides a construction method of a hard road shoulder of a road, which comprises the following steps: cleaning and leveling: cleaning garbage and protruding stones on the ground in a road shoulder area, and tamping original soil, so that the distance between the tamped road surface and the surface of the road is 80-200mm; materials are prepared, specifically, 60-83 parts of the tail dust of the asphalt mixing station, 8-31 parts of cement and 9-20 parts of sand are added into stirring equipment, and the water-solid ratio is 0.22-0.35; feeding: continuously adding the mixed materials into a feeding hole of a slip form machine; and paving the hard road shoulder: using a slip form machine to travel along the road surface in the cleaned and leveled area, and paving the hard road shoulder, so that the hard road shoulder with the thickness of 80-200mm is formed on the surface of the construction area. According to the technical scheme, compared with a traditional road shoulder construction process, the slip form process has the advantages that the construction process is greatly saved, the construction speed is high, the occupied site is small, and the structural integrity is high; in addition, a large amount of industrial solid waste-asphalt mixing station tail dust is applied to the raw materials, bulk application of the industrial solid waste is achieved, a new application direction of the asphalt mixing station tail dust is provided, and damage to the environment is further reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention generally relates to the field of road paving, and in particular to a construction method for a highway hard shoulder. Background Art

[0002] Hard shoulders are an important part of road design, usually referring to the hard surface on both sides of the road or outside the central dividing strip. On highways and some main roads, hard shoulders can be used as emergency parking strips for vehicles to temporarily stop in emergencies. In addition, hard shoulders can also be used as temporary lanes in traffic congestion to relieve traffic pressure. In addition to providing the necessary lateral safety margin for the lane and the lateral support of the lane pavement structure, they should be reinforced near villages and towns and on roads with heavy mixed traffic.

[0003] Moreover, professionals in different industries have different understandings of the use of hard shoulders. For designers, hard shoulders are used to protect lanes and allow rainwater to drain farther away from the lanes to prevent rainwater from seeping into and damaging lane facilities. For managers, hard shoulders provide safe havens. In case of emergencies, vehicles can be parked on the hard shoulders to avoid secondary accidents. For maintenance workers, hard shoulders can be used for parking, temporary storage of maintenance tools, or temporary storage of cleared garbage in disaster weather.

[0004] However, many roads currently have dirt shoulders, especially low-grade shoulders, such as township and village roads with asphalt pavement. Dirt shoulders are easily damaged by the erosion of rainwater, causing gullies on the road surface and even serious road collapse, which in turn affects the edge of the road surface and causes it to break and fall off. Summary of the invention

[0005] According to the present invention, in view of the problems existing in the above-mentioned prior art, a construction method of a highway hard shoulder is provided, and the construction method of a highway hard shoulder is characterized in that it comprises the following steps:

[0006] Clean and level the road, remove garbage and protruding stones from the shoulder area, and compact the original soil so that the compacted road surface is 80-200mm away from the highway surface;

[0007] Prepare the materials, add 60-83 parts of asphalt mixing plant tail dust, 8-31 parts of cement, 9-20 parts of sand into the mixing equipment, and the water-to-solid ratio is 0.22-0.35;

[0008] Feeding: continuously add the mixed materials into the feeding port of the slipform machine;

[0009] To pave the hard shoulder, a slipform machine is used to travel along the road surface in the cleaned and leveled area to pave the hard shoulder, so that a hard shoulder with a thickness of 80-200mm is formed on the surface of the construction area. With the above technical features, the use of the slipform process greatly saves construction procedures compared with the traditional shoulder construction process. The shoulder can be paved at one time only by the movement of the slipform machine, which is simple to operate and efficient. In addition, a large amount of industrial solid waste - tail dust from asphalt mixing stations is used in the raw materials, which realizes the large-scale application of industrial solid waste, provides a new direction for the application of tail dust from asphalt mixing stations, and further reduces damage to the environment.

[0010] In some embodiments, the following steps are added before the cleaning and leveling step: removing the original shoulder, removing the shoulders on both sides of the original road surface, and removing the shoulder width is not less than 0.75m. Therefore, for the road surface reconstruction section, the original road surface needs to be cleaned to ensure the normal operation of the sliding film machine, and 1.5 meters also meets the national standard for hard shoulders currently stipulated by the state.

[0011] In some embodiments, after the hard shoulder paving step, the following steps are added: embossing operation, within 10 minutes after the hard shoulder paving, the hard shoulder surface is embossed using embossing equipment. Therefore, using the above-mentioned proportion of materials, the friction performance of the road surface after maintenance is lower than that of the conventional concrete road surface. In order to ensure the safety of people walking or vehicles traveling, the embossing operation can improve the friction performance of the hard shoulder road surface.

[0012] In some embodiments, the following step is added after the embossing step: expansion joints are arranged along the width direction of the road surface and spaced along the length direction of the road surface. Thus, the expansion joints can prevent cracks from forming on the road surface due to climate change, thereby increasing the service life of the hard shoulder.

[0013] In some embodiments, the interval between adjacent expansion joints is 5-8 meters. Thus, by reasonably setting the interval between expansion joints, the occurrence of road cracking is reduced and the construction efficiency is also improved.

[0014] In some embodiments, the depth of the expansion joint is 1 / 2-1 / 3 of the overall thickness of the hard shoulder.

[0015] In some embodiments, the moving speed of the slipform machine during operation is 0-5.5 m / min. Due to the use of the above raw materials and proportions, the friction coefficient after curing is within a controllable range, so that when the slipform machine is running, the friction between the machine body and the material is reduced, making the material discharge smoother and smoother. Compared with the traditional material proportion, the operating speed of the slipform machine can be greatly improved, and the forming and quality of the hard shoulder will not be affected, which indirectly improves the construction efficiency.

[0016] In some embodiments, the friction coefficient of the hard shoulder after maintenance is 46-55 BPN. As a result, the raw material ratio is more delicate, making the sliding film machine discharge more smoothly, reducing the sliding film machine moving too fast and the occurrence of material adhesion, ensuring the efficiency of material demoulding and reducing the manpower consumption of later manual repair.

[0017] Compared with the prior art, the present invention has the following effects:

[0018] 1. Improved construction efficiency. Compared with traditional mold construction, the construction method of the sliding film machine greatly simplifies the construction process, reduces the construction period, and improves the paving efficiency. The paving and forming of the hard shoulder is achieved by only continuously feeding the sliding film machine with materials according to the preset ratio and controlling the speed of the sliding film machine;

[0019] 2. It provides a large-scale utilization of tail dust from asphalt mixing plants. In terms of paving materials, tail dust not only accounts for the largest proportion, but also meets the response standard of hard shoulder, thus providing a new direction for the application of tail dust from asphalt mixing plants;

[0020] 3. Reduced costs. Since the hard shoulder only uses dust from the mixing station, cement, sand and water, the material cost is saved to a great extent.

[0021] It should be understood that the contents described in the summary of the invention are not intended to limit the key or important features of the embodiments of the present disclosure, nor are they intended to limit the scope of the present disclosure. Other features of the present disclosure will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A schematic diagram of a new road construction method for a hard shoulder of a highway provided by a preferred embodiment of the present invention is shown;

[0023] Figure 2 A schematic diagram of a construction method for repairing an old hard shoulder road of a highway provided by a preferred embodiment of the present invention is shown.

[0024] Explanation of symbols

[0025] 1. Remove the original shoulder; 2. Clean and level; 3. Mix materials; 4. Feed materials; 5. Pave the hard shoulder; 6. Embossing operation; 7. Set expansion joints; 8. Sprinkle water for maintenance. DETAILED DESCRIPTION

[0026] Hereinafter, preferred embodiments (or implementation modes) of the present invention will be described in detail with reference to the accompanying drawings.

[0027] Figure 1 A schematic diagram of a new road construction method for a hard shoulder of a highway provided by a preferred embodiment of the present invention is shown, with reference to Figure 1As shown, a construction method for a highway hard shoulder mainly includes the following steps:

[0028] Cleaning and leveling 2. Excavators can be used to clean the basic road surface in the shoulder area, and the height of the foundation should be 80-200mm away from the height of the middle road surface. Secondly, the garbage and protruding stones on the basic road surface need to be cleaned. The cleaning work can be carried out in sections according to the length of the construction area to avoid being affected by environmental factors again during the construction process, causing garbage to fall on the construction road surface, ensuring that the construction road surface is clean and flat. After cleaning the garbage and stones, the construction road surface is compacted to ensure that the foundation is stable and firm, reducing the occurrence of subsequent road collapse.

[0029] Mix materials 3, prepare concrete pavement materials used by the sliding film machine, including 60-83 parts of asphalt mixing plant tail dust, 8-31 parts of cement, 9-20 parts of sand, 15-50 parts of water, water-solid ratio maintained between 0.22-0.35, and mortar consistency value of 35cm-50cm, then put the proportioned materials into the mixing equipment for mixing. The mixing equipment can adopt a fixed mixing method according to the construction length, or a mobile mixing method to reduce the impact of the feeding on the efficiency of the sliding film machine.

[0030] Among them, mixing station tail dust mainly refers to the tail fine waste generated in the process of producing hot mix asphalt in asphalt mixing station and collected by bag dust removal, mainly including stone powder, soil, residues from aggregate drying system and heavy oil combustion, etc. These particles cannot be effectively collected and processed, and are very easy to fly into the surrounding environment, which not only pollutes the surrounding air quality, but also has adverse effects on the surrounding vegetation, buildings, and human health. Therefore, using mixing station tail dust as raw material not only provides a pollution-free way to use mixing station tail dust, but also greatly reduces the overall cost of the concrete material.

[0031] Cement can be at least one of P.O42.5 and P.O52.5, wherein P.O42.5 is a medium-strength cement, which has the characteristics of high early strength, short setting time, fast hydration and hardening speed, low water seepage rate, small shrinkage rate, good wear resistance, etc. P.O52.5 also has the characteristics of high early strength, in addition, it has good wear resistance, high anti-seepage and anti-erosion performance, stable performance, and is suitable for configuring high-performance and high-grade concrete. The specific cement used can be determined according to the specific pavement parameters required by the shoulder pavement.

[0032] Sand can be at least one of medium sand and coarse sand. Among them, medium sand has a filling and cementing effect, and can reduce segregation and stratification in the mixture, ensuring the uniformity of the mixture. Compared with fine sand, medium sand has larger particles and higher bonding properties, thereby improving the strength of concrete. Coarse sand has larger particles and stronger bite force between particles. It has higher strength when mixed with cement. It can also reduce the shrinkage deformation of cement paste to a certain extent, thereby reducing the risk of cracks caused by shrinkage in concrete. In some cases, the appropriate use of coarse sand can also reduce the amount of cement used.

[0033] Feeding 4. Determine the mixing method according to the construction length. If the construction length is within the range of 0-15 meters, a fixed mixing method can be used, and the mixed materials can be added into the feeding port of the sliding film machine through manual feeding to provide shoulder paving for the sliding film machine. If the construction length is greater than 15 meters, a concrete mixer truck can be used to continuously supply materials to the sliding film machine to ensure the continuous construction and movement of the sliding film machine, thereby ensuring the construction efficiency of the sliding film machine.

[0034] Pave the hard shoulder 5, start the sliding film machine, and make it move slowly along the planned path to ensure the stability of continuous discharge of concrete materials and the integrity and flatness of the demoulding of the shoulder area.

[0035] Among them, the traveling speed of the sliding film machine can be adjusted according to the ratio of materials, specifically controlled at 0-5.5m / min. Since concrete materials mixed with mixing station tail dust are used, and the particle size of the mixing station tail dust is mostly less than 0.075mm, and as the first proportion of concrete materials, the texture is finer than traditional concrete materials, and it is not easy to stick to the mold of the sliding film machine, which greatly improves the integrity and smoothness of the shoulder forming. Compared with traditional concrete materials, its advantages can indirectly increase the traveling speed of the sliding film machine and ensure the integrity and smoothness of the shoulder pavement forming.

[0036] Embossing operation 6. Within 10 minutes after the shoulder is paved, use embossing equipment to emboss the shoulder surface. Since the concrete material used for paving the hard shoulder is mixed with a large amount of dust from the mixing station, the friction coefficient of the road surface after maintenance is much lower than that of the traditional concrete road surface. Therefore, embossing can increase the friction coefficient of the road surface and ensure the safety of people walking and vehicles traveling. Generally, the friction coefficient of the hard shoulder after maintenance is 90-100BPN, which is much higher than that of the untreated hard shoulder surface.

[0037] Expansion joints 7 are set. After embossing, expansion joints need to be set along the length direction of the road surface and in the width direction of the hard shoulder. The interval length of the expansion joints is 5-8 meters, and the depth of each expansion joint is controlled at 1 / 2-1 / 3 of the overall thickness of the hard shoulder to prevent cracks in the road surface caused by climate temperature changes, thereby extending the service life of the road surface.

[0038] Watering maintenance 8. After the compression joint construction, select appropriate watering vehicles or tools according to the maintenance area and needs to ensure the normal operation of the watering system; the shoulder can be maintained by sprinkling water and laying film on the shoulder. After the watering is completed, check the wetness of the surface of the maintenance object to ensure that the expected moisturizing effect is achieved.

[0039] Figure 2 A schematic diagram of a construction method for repairing an old hard shoulder road of a highway provided by a preferred embodiment of the present invention is shown, with reference to Figure 2 As shown, a construction method for a highway hard shoulder mainly includes the following steps:

[0040] Remove the original shoulder and use mechanical equipment to dig out the shoulder area of ​​the original road surface, and make the height of the excavated road surface foundation 80-200mm from the road surface, and the width of the excavated shoulder is not less than 0.75m.

[0041] For cleaning and leveling, excavators can be used to clean the basic road surface in the shoulder area, and the height of the foundation should be 80-200mm away from the height of the middle road surface. The garbage and protruding stones on the basic road surface should be cleaned. The cleaning work can be carried out in sections according to the length of the construction area to avoid being affected by environmental factors again during the construction process, causing garbage to fall on the construction road surface, ensuring that the construction road surface is clean and flat. After cleaning the garbage and stones, the construction road surface should be compacted to ensure that the foundation is stable and firm, reducing the occurrence of subsequent road collapse.

[0042] Mix materials and prepare pavement materials used by the sliding film machine, including 60-83 parts of asphalt mixing plant dust, 8-31 parts of cement, 9-20 parts of sand, and keep the water-to-solid ratio between 0.22-0.35. Put the mixed materials into the mixing equipment for mixing.

[0043] For feeding, the mixing method is determined according to the construction length. If the construction length is within the range of 0-15 meters, a fixed mixing method can be used. Compared with the manual feeding method, the mixed materials are added into the feeding port of the sliding film machine for shoulder paving of the sliding film machine. If the construction length is greater than 15 meters, a concrete mixer truck can be used to continuously supply materials to the sliding film machine to ensure the continuous construction and movement of the sliding film machine, thereby ensuring the construction efficiency of the sliding film machine.

[0044] When paving the hard shoulder, start the slip film machine and make it move slowly along the planned path to ensure the stability of continuous material discharge and the integrity and flatness of the demoulding of the shoulder area.

[0045]

Reference Standard

[0046] According to the new version of "Highway Engineering Technical Standards" implemented in 2015, the standard for hard shoulders will be based on function, specifically: the width of the right hard shoulder of expressways and first-class highways with trunk functions is generally 3 meters, with a minimum of 1.5 meters. The width of secondary roads in towns and villages can be determined according to actual conditions, but the relevant performance parameters of the hard shoulder are not specifically calibrated. However, the hard shoulder is also a highway area and meets the relevant highway specifications, so the compressive strength, flexural strength, water seepage resistance coefficient, antifreeze performance, and anti-friction coefficient will be used as performance indicators to judge whether the hard shoulder is qualified. The following is a specific embodiment.

[0047] Flexural strength:

[0048] According to the Highway Cement Concrete Pavement Design Specification, the design strength of cement concrete should adopt the flexural strength at 28 days of age. The standard value of the material flexural strength required for each traffic load level shall not be lower than that specified in Table 1.

[0049] Table 1:

[0050]

[0051] A road material that can be constructed using a sliding membrane. Since this material does not belong to cement concrete, it is closer to cement-stabilized materials. In addition, this material is a low-strength solid waste recycling material and is only used for low-grade roads in towns, villages, etc., so it meets the light traffic load level and takes 4MPa as the reference standard.

[0052] Anti-friction performance:

[0053] China's current standards stipulate that the anti-skid ability of the road surface should be characterized by measuring the swing value BPN with a pendulum instrument or measuring the lateral force coefficient SFC with a friction coefficient measuring vehicle. When BPN is greater than 42, or SFC is less than 0.5, the anti-skid ability of the road surface is excellent. Since the road material constructed by this sliding film is only used in the hard shoulder area of ​​towns and villages, it is mainly used for convenient transportation such as people, bicycles, and electric vehicles. The traffic load is limited and the vehicle speed is limited, so the anti-friction property of the road surface is based on 40BPN as the standard.

[0054] Antifreeze performance:

[0055] The frost resistance of concrete is generally expressed in frost resistance grades. The frost resistance grade is determined by the maximum number of freeze-thaw cycles that a 28-day-old test block can withstand when the compressive strength decreases by no more than 25% and the mass loss does not exceed 5% after absorbing water and being subjected to repeated freeze-thaw cycles. GBJ50164-92 divides concrete into the following frost resistance grades: F10, F15, F25, F50, F100, F150, F200, F250, F300, etc., which respectively indicate that the concrete can withstand 10, 15, 25, 50, 100, 150, 200, 250 and 300 repeated freeze-thaw cycles. Concrete with frost resistance grade ≥ F50 is called frost-resistant concrete.

[0056] Since this material does not belong to cement concrete, it is closer to cement stabilized materials, that is, semi-rigid materials, and its antifreeze performance is inferior to that of cement concrete. Moreover, this material belongs to solid waste recycling materials with lower strength. The purpose is to use its low cost to build shoulder auxiliary structures with less bearing function of low-grade roads. According to GBJ50164-92, its antifreeze coefficient is F15 as a qualified reference.

[0057] Water resistance:

[0058] A road material that can be constructed with sliding membrane. Since it is not cement concrete, its anti-permeability test is mainly carried out by referring to the asphalt pavement permeability coefficient test method in the "Highway Roadbed and Pavement Field Test Regulations". The general design annual average permeability is required to be 0.5L / (s·m 2 ), the designed annual average permeability coefficient cannot exceed 2.0mm / s.

[0059] Embodiment 1:

[0060] According to weight, take 60 parts by weight of mixing station tail dust, 8 parts by weight of 52.5 grade ordinary Portland cement, and 9 parts by weight of coarse sand, with a water-to-solid ratio of 0.22.

[0061] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 14.8MPa.

[0062] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4.8MPa.

[0063] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0064] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0065] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0066] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 50.8 BPN. See Table 3 for specific data.

[0067] The speed of the sliding film machine is 0-5.7m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0068] Embodiment 2:

[0069] According to weight, take 70 parts by weight of mixing station tail dust, 8 parts by weight of 52.5 grade ordinary Portland cement, and 9 parts by weight of coarse sand, with a water-to-solid ratio of 0.22.

[0070] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 15.3MPa.

[0071] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4.4MPa.

[0072] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0073] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0074] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0075] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 48.6BPN. Specific data are shown in Table 3.

[0076] The speed of the sliding film machine is 0-5.8m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0077] Embodiment 3:

[0078] According to weight, take 83 parts by weight of mixing station tail dust, 8 parts by weight of 52.5 grade ordinary Portland cement, and 9 parts by weight of coarse sand, with a water-to-solid ratio of 0.22.

[0079] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 14.9MPa.

[0080] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4.1MPa.

[0081] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0082] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0083] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0084] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 46.4BPN. Specific data are shown in Table 3.

[0085] The speed of the sliding film machine is 0-5.87m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0086] Embodiment 4:

[0087] According to weight, take 75 parts by weight of mixing station tail dust, 25 parts by weight of 52.5 grade ordinary Portland cement, and 10 parts by weight of coarse sand, with a water-to-solid ratio of 0.26.

[0088] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 18.56MPa.

[0089] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4MPa.

[0090] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0091] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0092] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0093] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 49.1BPN. Specific data are shown in Table 3.

[0094] The speed of the sliding film machine is 0-5.6m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0095] Embodiment 5:

[0096] According to weight, take 75 parts by weight of mixing station tail dust, 25 parts by weight of 52.5 grade ordinary Portland cement, and 20 parts by weight of coarse sand, with a water-to-solid ratio of 0.26.

[0097] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 18.56MPa.

[0098] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4MPa.

[0099] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0100] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0101] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0102] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 53.9 BPN. See Table 3 for specific data.

[0103] The speed of the sliding film machine is 0-5.7m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0104] Embodiment 6:

[0105] According to weight, take 75 parts by weight of mixing station tail dust, 15 parts by weight of 52.5 grade ordinary Portland cement, and 20 parts by weight of coarse sand, with a water-to-solid ratio of 0.26.

[0106] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 18.3MPa.

[0107] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4.4MPa.

[0108] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0109] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0110] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0111] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 50.2BPN. Specific data are shown in Table 3.

[0112] The speed of the sliding film machine is 0-5.5m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0113] Embodiment 7:

[0114] According to weight, take 75 parts by weight of mixing station tail dust, 21 parts by weight of 52.5 grade ordinary Portland cement, and 20 parts by weight of coarse sand, with a water-to-solid ratio of 0.26.

[0115] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 21.67MPa.

[0116] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4.4MPa.

[0117] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0118] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0119] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0120] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 52.3BPN. Specific data are shown in Table 3.

[0121] The speed of the sliding film machine is 0-5.6m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0122] Embodiment 8:

[0123] According to weight, take 75 parts by weight of mixing station tail dust, 31 parts by weight of 52.5 grade ordinary Portland cement, and 20 parts by weight of coarse sand, with a water-to-solid ratio of 0.26.

[0124] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 24.56MPa.

[0125] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4.6MPa.

[0126] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0127] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0128] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0129] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 54.2BPN. Specific data are shown in Table 3.

[0130] The speed of the sliding film machine is 0-5.56m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0131] Embodiment 9:

[0132] According to weight, take 75 parts by weight of mixing station tail dust, 21 parts by weight of 52.5 grade ordinary Portland cement, and 20 parts by weight of coarse sand, with a water-to-solid ratio of 0.28.

[0133] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 21.98MPa.

[0134] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4.3MPa.

[0135] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0136] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0137] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0138] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 53.6BPN. Specific data are shown in Table 3.

[0139] The speed of the sliding film machine is 0-5.64m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0140] Embodiment 10:

[0141] According to weight, take 75 parts by weight of mixing station tail dust, 21 parts by weight of 52.5 grade ordinary Portland cement, and 20 parts by weight of coarse sand, with a water-to-solid ratio of 0.35.

[0142] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 22.79MPa.

[0143] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4.2MPa.

[0144] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0145] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material of the present invention that can be constructed using a sliding film after 15 freeze-thaw cycles is less than 5%.

[0146] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0147] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 46.5BPN. Specific data are shown in Table 3.

[0148] The speed of the sliding film machine is 0-5.54m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0149] According to the test results in Table 3, the concrete materials meet the national road standards in terms of 28d compressive strength, 28d flexural strength, water seepage resistance, antifreeze coefficient and anti-friction coefficient. However, due to the use of a sliding film machine for road construction, the anti-friction coefficient is between greater than 46 and less than 55, which can meet the working speed of the sliding film machine at 0-5.5m / min, and ensure the integrity and flatness of the demoulding of the concrete materials, greatly reducing the manpower consumption of manual post-finishing. Compared with the working speed of 0-5m / min of the traditional sliding film machine, it greatly increases the work efficiency and the yield rate.

[0150] Comparative Example 1:

[0151] According to weight, take 25 parts by weight of 52.5 grade ordinary Portland cement and 70 parts by weight of coarse sand, and the water-to-solid ratio is 0.26.

[0152] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 53MPa.

[0153] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 7.1MPa.

[0154] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it was measured that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0155] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material that can be constructed using a sliding film of the present invention after 15 freeze-thaw cycles is less than 5%.

[0156] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0157] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the friction coefficient of the hard shoulder material that can be constructed with a sliding film is 89.2BPN. Specific data are shown in Table 3.

[0158] The speed of the sliding film machine is 0-3.2m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0159] By comparing and analyzing the test results of Table 4 with those of Table 3, Comparative Example 1 is a traditional concrete material. The concrete material meets the national road standards in terms of 28d compressive strength, 28d flexural strength, water resistance, antifreeze coefficient, and anti-friction coefficient. However, the sand particle size is large, and after mixing with cement, the surface is rough. The friction coefficient after curing is much higher than that of the hard shoulder material after curing with concrete materials using mixing station tail dust, which limits the working speed of the sliding film machine and the flatness of the road surface. After the concrete material is demolded from the sliding film machine, its integrity and flatness are worse than those of the concrete materials in Examples 1-10, which increases the consumption of manual repair and reduces the overall construction efficiency.

[0160] Comparative Example 2:

[0161] According to weight, take 50 parts by weight of mixing station tail dust, 8 parts by weight of 52.5 grade ordinary Portland cement, and 9 parts by weight of coarse sand, with a water-to-solid ratio of 0.22.

[0162] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 13.59MPa.

[0163] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 3.54MPa.

[0164] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0165] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material that can be constructed using a sliding film of the present invention after 15 freeze-thaw cycles is less than 5%.

[0166] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0167] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 69.8 BPN. See Table 3 for specific data.

[0168] The speed of the sliding film machine is 0-5.1m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0169] By comparing and analyzing the test results in Table 4 and Table 3, it is found that compared with Example 1, the tail dust content of the mixing station of Comparative Example 2 is reduced, resulting in the 28d compressive strength of the concrete being lower than 14MPa, and the 28d flexural strength being lower than 4, which does not meet the pavement strength standard.

[0170] Comparative Example 3:

[0171] According to weight, take 70 parts by weight of mixing station tail dust, 25 parts by weight of 52.5 grade ordinary Portland cement, and 30 parts by weight of coarse sand, with a water-to-solid ratio of 0.26.

[0172] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 23.5MPa.

[0173] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4.4MPa.

[0174] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0175] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material that can be constructed using a sliding film of the present invention after 15 freeze-thaw cycles is less than 5%.

[0176] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0177] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 81.2. Specific data are shown in Table 3.

[0178] The speed of the sliding film machine is 0-5.43m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0179] By comparing and analyzing the test results of Table 4 with those of Table 3, it is found that compared with Example 5, the tail dust content of Comparative Example 3 is reduced and the coarse sand content is increased, resulting in the friction coefficient of the road surface after maintenance being higher than 80, which limits the working speed of the sliding film machine, reduces the smoothness of the road surface, and generates burrs intermittently, requiring subsequent manual repair.

[0180] Comparative Example 4:

[0181] According to weight, take 70 parts by weight of mixing station tail dust, 40 parts by weight of 52.5 grade ordinary Portland cement, and 10 parts by weight of coarse sand, with a water-to-solid ratio of 0.26.

[0182] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 48.5MPa.

[0183] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 6.8MPa.

[0184] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0185] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material that can be constructed using a sliding film of the present invention after 15 freeze-thaw cycles is less than 5%.

[0186] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the strength loss of the hard shoulder material of the present invention that can be constructed using a sliding film is less than 25% after 15 freeze-thaw cycles.

[0187] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 83.2. Specific data are shown in Table 3.

[0188] The speed of the sliding film machine is 0-5.3m / min. The concrete material discharge is stable, with high forming rate, high integrity rate and high flatness.

[0189] By comparing and analyzing the test results of Table 4 with those of Table 3, it is found that compared with Example 4, the cement content of Comparative Example 4 is increased, resulting in increased compressive strength and flexural strength of the concrete, but also increasing the friction coefficient of the road surface, which limits the working speed of the sliding film machine, reduces the smoothness of the road surface, and generates burrs intermittently, requiring subsequent manual repair.

[0190] Comparative Example 5:

[0191] According to weight, take 70 parts by weight of mixing station tail dust, 25 parts by weight of 52.5 grade ordinary Portland cement, and 10 parts by weight of coarse sand, with a water-to-solid ratio of 0.41.

[0192] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day compressive strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 24.5MPa.

[0193] According to the test of "T0506-2005 Cement Mortar Strength Test Method", the 28-day flexural strength of the hard shoulder material of the present invention that can be constructed with sliding film is measured to be 4.7MPa.

[0194] According to the anti-seepage performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is found that the hard shoulder material of the present invention that can be constructed using a sliding film has no obvious water seepage phenomenon.

[0195] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", it is measured that the mass loss of the hard shoulder material that can be constructed using a sliding film of the present invention after 15 freeze-thaw cycles is less than 5%.

[0196] According to the antifreeze performance test in JGJ / T70-2009 "Standard for Test Methods for Basic Properties of Building Mortar", it is measured that the strength loss of the hard shoulder material that can be constructed using a sliding film of the present invention after 15 freeze-thaw cycles is less than 25%.

[0197] According to JT / T 763-2017 "Pendulum Friction Coefficient Tester", the parallel friction coefficient of the hard shoulder material that can be constructed with a sliding film according to the present invention is 50. See Table 3 for specific data.

[0198] The demoulding integrity rate of concrete materials is low and local collapse is prone to occur.

[0199] By comparing and analyzing the test results in Table 4 with those in Table 3, although the concrete material meets the national road standards in terms of 28d compressive strength, 28d flexural strength, water resistance, antifreeze coefficient and anti-friction coefficient, the increase in water-solid ratio causes partial collapse of the concrete pavement after demoulding during the operation of the sliding film machine, which reduces the integrity of the hard shoulder.

[0200] A road material that can be constructed using a sliding film. This material does not belong to cement concrete, but is closer to cement-stabilized materials, i.e., semi-rigid materials. Its antifreeze performance is inferior to that of cement concrete. This material is a solid waste recycling material with lower strength. The purpose is to use it to build shoulder auxiliary structures with less load-bearing functions of low-grade roads at a low cost. This material is only used in the shoulder area of ​​Class IV highways. With the sliding film construction process, a hard shoulder with high integrity, high flatness, and less manual repair is paved. The material is reasonably proportioned to control the friction coefficient of the hard shoulder between 46-55BPN, thereby increasing the travel speed of the sliding film equipment, and improving construction efficiency while ensuring quality.

[0201] Table 3:

[0202]

[0203]

[0204] Table 4:

[0205]

[0206]

[0207] In the description of this specification, the terms "connection", "installation", "fixation" and the like should be understood in a broad sense. For example, "connection" can be a fixed connection, a detachable connection, or an integral connection; it can be a direct connection or an indirect connection through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0208] The above are only preferred embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for constructing a hard shoulder of a highway, characterized in that: The following steps are involved: Clean and level the road, remove garbage and protruding stones from the shoulder area, and compact the original soil so that the compacted road surface is 80-200mm away from the highway surface; Prepare the materials, add 60-83 parts of asphalt mixing plant tail dust, 8-31 parts of cement, 9-20 parts of sand into the mixing equipment, and the water-to-solid ratio is 0.22-0.35; Feeding: continuously add the mixed materials into the feeding port of the slipform machine; To pave the hard shoulder, use a slipform machine to drive along the road surface in the cleaned and leveled area to pave the hard shoulder, so that a hard shoulder with a thickness of 80-200mm is formed on the surface of the construction area.

2. A method for constructing a highway hard shoulder according to claim 1, characterized in that: Add the following steps before the cleanup and leveling steps: Remove the original shoulders, remove the shoulders on both sides of the original road surface, and the width of the removed shoulders shall not be less than 0.75m.

3. A method for constructing a hard shoulder of a highway according to claim 1 or 2, characterized in that: Add the following steps after the Pave Hard Shoulder step: Embossing operation: within 10 minutes after the hard shoulder is paved, use embossing equipment to emboss the surface of the hard shoulder.

4. A method for constructing a hard shoulder of a highway according to claim 3, characterized in that: Add the following steps after the Embossing step: Expansion joints are set up along the width of the road surface and at intervals along the length of the road surface.

5. A method for constructing a hard shoulder of a highway according to claim 4, characterized in that: The interval between adjacent expansion joints is 5-8 meters.

6. A method for constructing a hard shoulder of a highway according to claim 4, characterized in that: The depth of the expansion joint is 1 / 2-1 / 3 of the overall thickness of the hard shoulder.

7. A method for constructing a hard shoulder of a highway according to claim 1 or 2, characterized in that: The moving speed of the slipform machine during operation is 0-5.5 m / min.

8. A method for constructing a hard shoulder of a highway according to claim 1 or 2, characterized in that: The friction coefficient of the hard shoulder after maintenance is 46-55BPN.